Does Admission NT-ProBNP Increase the Prognostic Accuracy of GRACE Risk Score in the Prediction of Short-Term Mortality After Acute Coronary Syndromes? - Timóteo, AT (2017)
Submitted by Ana Quininha (ana.quininha@chlc.min-saude.pt) on 2017-04-19T09:34:54Z No. of bitstreams: 1 Acute Cardiac Care 236.pdf: 149047 bytes, checksum: 7cee0b6f46d28b14e6f26f14522d2595 (MD5)